Facile fabrication of binary g-C3N4/NH2-MIL-125(Ti) MOF nanocomposite with Z-scheme heterojunction for efficient photocatalytic H2 production and CO2 reduction under visible light - Ikreedeegh, Riyadh Ramadhan; Tasleem, Sehar; Hossen, Md Arif (Elsevier Ltd, 2024)
A binary g-C3N4/NH2-MIL-125(Ti) MOF nanocomposite was fabricated through a facile sonochemical-assisted thermal approach for enhanced photocatalytic H2 production and CO2 reduction under visible light. Compared to pure g-C3N4, the g-C3N4/MOF photocatalyst showed enhanced visible light absorption with promoted charge carrier separation which increased the H2 production rate and the CO2 reduction into CH4 and CO. This enhancement was attributed to the successfully constructed Z-scheme heterojunction in addition to the visible-active, large surface area and highly CO2 adsorbable NH2-MIL-125(Ti) MOF. The highest H2 production of 480 µmol g−1 was exhibited over the g-C3N4/NH2-MIL-125(Ti) nanocomposite with 20 wt% MOF. Similarly, the highest CO production rate of 338 µmol g−1 was achieved with 20 wt% MOF composite. However, for the CH4 product gas, it was observed that the highest production rate was attained with pure g-C3N4 which reveals the NH2-MIL-125(Ti) MOF selectivity towards CO production instead of CH4. Among all the investigated sacrificial agents for H2 production, methanol was the best. The performance of CO2 reduction process was found to be increasing with the pressure increase. Furthermore, the stability investigations revealed continuous productions of H2, CO and CH4 over the C3N4/MOF photocatalyst in multiple cyclic runs without any significant photocatalyst deactivation. This study provides new ideas for the fabrication of cheap, efficient and easy-synthesized nanomaterials for energy production and environmental remediation applications.